Crossing Kingdoms: How Can Art Open Up New Ways of Thinking About Science? - Szymanski, Erika; Bates, Tarsh; Cachat, Elise; Calvert, Jane; Catts, Oron; Nelson, Lenny J.; Rosser, Susan J.; Smith, Robert D. J.; Zurr, Ionat (Frontiers in Bioengineering and Biotechnology, 2020)
“Crossing Kingdoms” is an artist-led experiment in the biological fusion of mammalian and yeast cells and the cultural discussions of these phenomena. We present this collaboration as an experiment in responsible research and innovation (RRI), an institutionalized format for ensuring that researchers reflect on the wider social dimensions of their work. Our methods challenged us as researchers to reflect interdisciplinary collaboration and the possibility of innovating in biology for artistic purposes, challenged audiences to reflect on biological boundaries, and challenged both groups to reflect on what it means to be responsible in science. We conclude that our experiment in RRI was successful because we have asked unexpected questions—a contrast to RRI implemented as a standard protocol. Our experiment has implications for biologists and artists pursuing interdisciplinary collaborations with each other and for researchers thinking about implementing RRI as more than a box-ticking exercise.